Analysis of the Use of Instagram as a Platform in Learning English-Speaking Skill - Tauhid, Tauhid Sekhmaulana Ibrahim; Angga Ferry Ferdian; Ibrahim, Tauhid Sekhmaulana (Saniya Institute, 2023)
Technology is integral to schooling in the 4.0 industrial revolution. Technology impacts education, including pupils. Technology affects their sight, hearing, speech, and communication. This research seeks to understand Instagram use in English Bilingual Program. This research uses open interviews so respondents can clearly and thoroughly answer portion-specific questions. Students profit much from learning speaking on Instagram, according to the study. Most said (1) students trust themselves in speaking English, (2) they focus more on perfect grammar while speaking, (3) they can easily fix their friends' posts, and (4) unfavorable comments from friends push them to speak more clearly and fluently.